Entrepreneurial innovation problems associated with the dynamic growth of university spin-outs in China: a capabilities perspective. (13th September 2010) - Zhou, Yuan; Minshall, Tim; Hampden-Turner, Charles
This research aims to develop a capabilities-based conceptual framework in order to study the stage-specific innovation problems associated with the dynamic growth process of university spin-outs (hereafter referred to as USOs) in China. Based on the existing literature, pilot cases and five critical cases, this study attempts to explore the interconnections between the entrepreneurial innovation problems and the configuration of innovative capabilities (that acquire, mobilise and re-configure the key resources) throughout the lifecycle of a firm in four growth phases. This paper aims to contribute to the literature in a holistic manner by providing a theoretical discussion of USOs' development through adding evidence from a rapid growth emerging economy. To date, studies that have investigated the development of USOs in China recognised the heterogeneity of USOs in terms of capabilities still remain sparse. Addressing this research gap will be of great interest to entrepreneurs, policy makers and venture investors.